Conversion of biowastes to biomaterial: An innovative waste management approach. (September 2017) - Kannan, M. Bobby; Ronan, Karly
Graphical abstract: Highlights: Study demonstrates that hydroxyapatite can be potentially produced from biowastes. Eggshells and synthetic urine was used for hydroxyapatite synthesis. Solution pH and stirring influenced hydroxyapatite formation. Abstract: The study suggests that biowastes (eggshells and urine) can be potentially used as precursors to produce hydroxyapatite (HAp) biomaterial in a simple chemical process. A batch reactor was used in this work to produce HAp powder from eggshells and synthetic urine (SU). Fine powder of calcined eggshells was dissolved in water to produce aqueous calcium hydroxide. The solution was then mixed with concentrated SU in stoichiometric amounts corresponding to HAp (Ca/P molar ratio ∼ 1.67). The initial pH of the solution was alkaline (pH ∼ 8.5) and particles formed rapidly with slight mixing. Stirring the turbid solution for a longer period (72 h) did not show any visual change, but the particle size decreased slightly. When the pH of the solution was adjusted to 5, the solution was initially clear, but particle formation was apparent after 48 h stirring. It was noticed that at a slow stirring speed (100 rpm), film formation occurred on the solution, whereas at a higher stirring speed (500 rpm) no such film formation was observed. X-ray diffraction (XRD) analysis confirmed that the particles (formed at 500 rpm) were an amorphous calcium phosphate (CaP). Alkaline treatment at 80 °C for 2 h converted the amorphous CaP into HAp. Inductively coupled plasma mass spectrometry (ICP-MS) analysis of the particles (formed at 500 rpm) suggested that they are calcium-deficient HAp (Ca/P molar ratio 1.58).